Exploring pollution control in transboundary watersheds under the perspective of ecological compensation based on aggregate game - Gu, Jiawei; Zhang, Hui; Fang, Yinhai (Environmental science and pollution research international, 2024)
Pollution control in inter-provincial river basins involves many complex subjects, so it is difficult to effectively implement ecological compensation policies. To clarify the interest relationship among pollution control subjects and stimulate their willingness to cooperate in collaborative governance, this paper builds a multi-agent coordinated pollution control model based on the theory of aggregate game; explores the change of equilibrium action of a single pollution control agent and multi-actors, symmetric, and asymmetric situations under the influence of synergistic benefits; and studies the incentive mechanism design to maintain the cooperation of various agents. The research results show that an increase in the number of upstream firms would lead to a reduction in the incentive effects of downstream government compensation and an increase in the likelihood of “free-riding” and “coordination failure.” Synergy benefits vary positively with the degree of cooperation between government and enterprises, and higher synergy benefits can effectively compensate for the high transaction costs caused by multiple entities, alleviate the financial pressure on downstream governments, and increase the willingness of upstream and downstream entities to cooperate. In addition, focusing on wastewater reduction from core enterprises, such as heavy polluters can help improve the efficiency of regional emissions reduction, while having a catalytic effect on small enterprises.